Chain mail heterostructured hydrangea-like binary metal sulfides for high efficiency sodium ion battery. (September 2021) - Wang, Duo; Cao, Liang; Luo, Dan; Gao, Rui; Li, Haibo; Wang, Dandan; Sun, Guiru; Zhao, Zeyu; Li, Nan; Zhang, Yuting; Du, Fei; Feng, Ming; et al.
Abstract: Metal sulfides has long been deemed as advanced anode material for sodium-ion batteries (SIBs). However, the intrinsic defects (e.g., poor electrical conductivity and large volume variation) impede this material to reach the expectations of practical application. Here, we designed a unique chain mail Sb2 S3 /MoS2 heterostructure based on one step sulfidation of the hydrangea-like Sb2 MoO6 precursor and the obtained Sb2 S3 /MoS2 heterostructure exhibits large specific surface area as well as well-distributed heterointerfaces between Sb2 S3 and MoS2 among the whole composite. The introduction of band engineering modulates electronic states of heterointerfaces, which induced built-in electrical field for accelerated interfacial charge transportation. Meanwhile, the in-situ formed nitrogen-rich carbon chain mail can not only facilitate electron migration and stabilize the active interfaces of Sb/Mo/Na2 S intermediate phases, but also provide enhanced mechanical strength to accommodate volume expansion over sodiation, rendering admirable structure stability. Attributed to these superiorities, the as-developed SIBs exhibit an enhanced cycling performance of 411.5 mAh g -1 over 650 cycles at 5 A g -1 . This work opens a new pathway for the material engineering strategy to design chain mail heterostructured material towards excellent performance. Graphical Abstract: ga1 Highlights: Chain mail heterostructured hydrangea-like Binary Metal Sulfides (Sb2 S3 /MoS2 ) is prepared through on step sulfidation. The advantages of spatial confinement effects and multicomponent interaction. Na + storage mechanism has been clearly revealed by in-situ characterization. The heterostructure exhibits superior rate capability and excellent cycling stability as SIB anode.